1968
DOI: 10.1104/pp.43.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Electron Transport Systems of Aquatic Fungi. I. Leptomitus lacteus and Apodachlya punctata

Abstract: Abstract. The electron transport systems of 2 species of aquatic fungi, Leptomitus lacteus and Apodachlya punctata, contained cytochrome a-a3 (605 m,u), 2 b type cytochromes (564 and 557 mju), c type cytochrome (551 mg), and flavoprotein, but they appeared to lack cytochrome c.. Reduced-minus-oxidized difference spectra and difference spectra in the presence of antimycin A or cyanide were used to characterize these systems. Studies with the electron microscope revealed that hyphae of Leptomitus lacteus contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Absorbance after reduction with dithionite showed additional peaks at 558 and 564 nm, the contribution of the b ‐haems of cytochrome b . Similar spectra were obtained with oomycete mycelia and submitochondrial particles . As the b L ‐haem has a split alpha‐band that overlaps the signal of the b H ‐haem, the contributions of the different b ‐haems could not be distinguished .…”
Section: Resultsmentioning
confidence: 61%
“…Absorbance after reduction with dithionite showed additional peaks at 558 and 564 nm, the contribution of the b ‐haems of cytochrome b . Similar spectra were obtained with oomycete mycelia and submitochondrial particles . As the b L ‐haem has a split alpha‐band that overlaps the signal of the b H ‐haem, the contributions of the different b ‐haems could not be distinguished .…”
Section: Resultsmentioning
confidence: 61%
“…Further data obtained with improved spectrophotometric techniques led Lindenmayer (7) to suggest that, in general, the cytochrome system of the fungi is remarkably similar to that of mammalian and avian cells and unlike the systems found in bacteria and in the mitochondrial of green plants. However, more recent work has shown that the cytochrome systems of biflagellate aquatic fungi belonging to the class Oomycetes differ substantially from that of yeast (3,4,10). The purpose of the present study was to compare the cytochrome systems found in the posteriorly uniflagellate fungi (Chytridiomycetes) with those in the biflagellate fungi (Oomycetes).…”
mentioning
confidence: 94%